Physicochemical Properties of Epoxy Resin-Based and Bioceramic-Based Root Canal Sealers - Ju Kyung Lee; Sang Won Kwak; Jung-Hong Ha; WooCheol Lee; Hyeon-Cheol Kim (Bioinorganic Chemistry and Applications)
Three bioceramic sealers (EndoSequence BC sealer, EndoSeal MTA, and MTA Fillapex) and three epoxy resin-based sealers (AH-Plus, AD Seal, and Radic-Sealer) were tested to evaluate the physicochemical properties: flow, final setting time, radiopacity, dimensional stability, and pH change. The one-way ANOVA and Tukey’s post hoc test were used to analyze the data (P=0.05). The MTA Fillapex sealer had a highest flow and the BC Sealer presented a flow significantly lower than the others (P<0.05). The BC Sealer and MTA Fillapex samples were not set in humid incubator condition even after one month. EndoSeal MTA had the longest setting time among the measurable materials and Radic-Sealer and AD Seal showed shorter setting time than the AH-Plus (P<0.05). AH-Plus and EndoSeal MTA showed statistically higher values and MTA Fillapex showed statistically lower radiopacity (P<0.05). BC Sealer showed the highest alkaline pH in all evaluation periods. Set samples of 3 epoxy resin-based sealers and EndoSeal MTA presented a significant increase of pH over experimental time for 4 weeks. In conclusion, the bioceramic sealer and epoxy resin-based sealers showed clinical acceptable physicochemical properties, but BC Sealer and MTA Fillapex were not set completely.